Synthesis of silane- and quaternary ammonium-bearing copolymers and application as a coating resin on cotton fabric - Martin, Ayse; Guler, Nazgul; Yerli, Ilknur; Hancer, Hande; Ozbek, Tulin; Eren, Tarik (Tubitak Scientific & Technological Research Council Turkey, 2023)
In this study, silane and quaternary ammonium functional methacrylate monomers were synthesized and used to construct a copolymer using an emulsion polymerization technique to control the reaction rate. The copolymer was then designed using different ratios of silane and quaternary ammonium groups to investigate the relationship between the structure and properties. The presence of the ethoxy silane group in the copolymer series provided covalent bonding through the silanol group onto cotton fabric. The presence of cationic groups also helped to cover the fabric surface. After coating the cotton textile fabric, the resistance of the dye on the fabric surface to friction was assessed and tests were conducted on washing, rubbing, water, and light fastness. Finally, the textile surfaces were investigated for their antibacterial activity against Staphylococcus aureus and Escherichia coli. It was observed that the copolymer series showed >99% killing efficiency against S. aureus but had no effect on E. coli.
Keywords: Cationic copolymer; polysiloxanes; fastness properties; dyeing properties; antibacterial activity; FASTNESS; POLYMER; Chemistry; Engineering